2013
DOI: 10.3892/mmr.2013.1407
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin: A potential marker in chronic peripheral arterial disease

Abstract: Abstract. Neopterin is a marker of macrophage activation that has exhibited high plasma levels in atherosclerotic diseases including coronary heart disease and critical limb ischemia. The role of neopterin in chronic peripheral arterial disease (PAD) has yet to be elucidated. In the present study, neopterin (Ν) serum concentrations were analyzed in asymptomatic (AsP) and symptomatic (SyP) patients with PAD as well as controls (C). In total 120 subjects, 40 AsP [ankle brachial index (ABI) ≤0.90], 40 SyP (ABI ≤0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The results also revealed an indirect correlation between neopterin levels, CD and ABI, where an increase in neopterin values was associated with a significant decrease of ABI. Similar results have been reported by Signorelli et al and Barani J. et al [ 28 , 61 , 62 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results also revealed an indirect correlation between neopterin levels, CD and ABI, where an increase in neopterin values was associated with a significant decrease of ABI. Similar results have been reported by Signorelli et al and Barani J. et al [ 28 , 61 , 62 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 91%
“…Neopterin, a member of the pteridine family, is an indicator of macrophage activation [26,27]. Several investigators have reported a relationship between neopterin and atherosclerosis plaque progression or instability [28]. Beta 2-macroglobulin (B2-MG), a component of the major histocompatibility complex class I molecule, is an acute-phase reactant protein, whose levels were described as elevated in patients with carotid artery intima-media thickening and arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…While neopterin has been measured repeatedly as an assessment of macrophage activation and infiltration for several decades [ 5 , 48 , 61 , 62 , 63 ], complete estimation of immune activation through total neopterin analysis has limited transparency for clinical outcomes. In 1989, Fuchs et al [ 16 ] measured neopterin plus 7,8-dihydroneopterin in HIV patients, suggesting that both provide equal potential for clinical diagnosis.…”
Section: Clinical Effectiveness Of Neopterin and Total Neopterinmentioning
confidence: 99%
“…Contrasting results suggest that its accumulation may be intensity-dependent [ 76 , 77 ], as the impacts and total running distance during a game of rugby strongly correlate with the observed increase in neopterin and total neopterin concentration [ 73 ]. Recently, neopterin has also been used to assess the positional demands of professional rugby players [ 78 ], and used to evaluate the effectiveness of post-game rugby union recovery interventions [ 79 ], the efficacy of cold water immersion [ 1 , 2 , 3 ], stress perturbations associated with ischemic preconditioning [ 4 ], and the monitoring of season-long stress fluctuations in professional rugby players [ 5 ].…”
Section: Clinical Effectiveness Of Neopterin and Total Neopterinmentioning
confidence: 99%
See 1 more Smart Citation